C++ interactive course : fast mastery of C++ - Lafore, Robert ([S.l.] : Waite Group Pr, 1998)
Teaches object-oriented programming in C++++ without assuming prior programming knowledge, dividing the course into small lessons devoted to specific topics and covering the newest features including the Standard Template Library. Original. (Beginner).